Electrochemiluminescence sensor based on GDYO-QD@M-ZnO and its application in the detection of free radicals and antioxidants - Tian, Gang; Yang, Cong; Tian, Yihang; Wang, Zihuan; Dang, Yannan (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
In view of the problems such as low luminous efficiency, poor stability and weak anti-interference ability of traditional electrochemiluminescence sensors, this study prepared graphdiyne oxide quantum dots by acid oxidation method and synthesized metal-organic skeleton derived zinc oxide by high-temperature calcination. The two were combined to construct a new ECL sensor. It is used for detecting free radicals and antioxidants such as vitamin C, trixerutin, and metformin hydrochloride. The results showed that GDYO-QD was successfully combined with M-ZnO. The constructed sensor has excellent electronic transmission ability, and the electrochemiluminescence signal is significantly enhanced compared with a single material, and has good detection performance for the target analyte. This study provides new ideas and practical tools for developing high-performance electrochemiluminescence sensors and effectively detecting free radicals and antioxidants.